Gender Stereotypes and Spatial Ability: Do Males Really Perform Better? - Saputra, Andari (Education, Science, and Technology International Conference, 2025)
Numerous studies have shown that gender differences in spatial ability can be influenced by biological, social, and environmental factors. Information processing theory suggests that males tend to rely more on visuospatial working memory, whereas females are more likely to use strategies based on verbal working memory, which may impact their performance in spatial tasks. This study aims to analyze the differences in spatial ability between male and female students. A quantitative approach was employed, involving 78 students aged 15 to 17 from three schools in Bandung, Indonesia. The t-test results indicated a significant difference in spatial ability between males and females (p = 0.008), with males demonstrating superior spatial skills. However, the overlapping distribution of scores suggests that some females possess spatial abilities equivalent to or even higher than some males. Therefore, although males tend to excel in certain aspects of spatial ability, these differences are not absolute and may be influenced by external factors, environmental conditions, and varying learning opportunities among individuals.